A dynamic study on serum biomarkers and kidney injury in a gosling model of hyperuricemia - Yuanjing Chen; Haiming Yang; Zhiyue Wang (Poultry Science)
Hyperuricemia, a metabolic disorder characterized by elevated serum uric acid levels, poses significant challenges to poultry health and productivity. This study aimed to establish a hyperuricemia model in goslings through a multi-factorial induction approach using a high-purine, high-protein, and high-calcium diet, to investigate its dynamic progression, serological markers, and renal pathology. A total of 160 male Sanhua goslings were randomly assigned to control and model groups and fed either a basal diet or a high-purine, high-protein, and high-calcium diet for 18 days.Key findings revealed significant elevations in serum uric acid, creatinine, and urea nitrogen levels in the model group from day 5 onward, peaking on day 13 (p < 0.01). Activities of xanthine oxidase and adenosine deaminase were consistently higher in the model group, indicating enhanced purine metabolism and oxidative stress. Histopathological analysis showed progressive renal damage, including tubular degeneration, interstitial fibrosis, and glomerular injury, becoming evident by day 7 and severe by day 13. Ultrastructural examination further revealed mitochondrial dysfunction, podocyte effacement, and basement membrane disruption in the model group. Behavioral abnormalities, such as reduced mobility and the ''shrinking neck'' phenomenon, were observed from day 9, reflecting systemic disease severity.The dynamic expression of fibrosis-related markers, including Col-1, Col-3, and α-SMA, demonstrated the progression of renal fibrosis and extracellular matrix remodeling. These findings identify biomarkers for hyperuricemia progression and suggest potential therapeutic targets. This study establishes a comprehensive framework for understanding hyperuricemia-associated renal pathology and lays the groundwork for developing strategies to mitigate its impact on poultry health and productivity.